Daur Ulang Sampah Plastik Untuk Pengembangan Produk Souvenir Khusus Kota Surakarta - Adam Wahida; Figur Rahman Fuad (Institut Seni Indonesia Denpasar, 2022)
This study aims to describe the development of souvenir products characteristic of the city of Surakarta using recycled plastic waste materials to support the Eco-Cultural City movement. Through this movement, the local government of Surakarta involves community participation to make Surakarta a cultural city with environmental insight that is creative economically, socially, and culturally. The programs that have been implemented include mobilizing the community by establishing a Waste Bank. Public awareness and participation in managing waste are integrated with the development of creative industries that are environmentally sound through the creative and innovative use of waste recycling into souvenir products typical of the city of Surakarta. This study uses development research methods with the following steps: 1) data collection, 2) initial product development, 3) initial product testing, and 4) major product improvement. The results of this study were: 1) identified the types of waste used as materials for making souvenir products, 2) the creation of various souvenir products with the basic idea of Canthik Rajamala form using recycled plastic waste materials. The conclusions of this study are: 1) plastic waste has great potential to be managed as materials for making souvenir products. 2) the resulting souvenir products have the characteristics of the city of Surakarta. Thus, the results of this study are expected to have an impact, including 1) growing public awareness in protecting the natural environment and local culture, 2) developing creative industries with character and environmental insight, 3) increasing the image of a cultural city that is creative and environmentally friendly.